Membangun Hubungan yang Positif melalui Komunikasi yang Efektif - Zuliana Sari; Sakinah Sakinah; Mufaro’ah Mufaro’ah (Institut Nalanda, 2024)
Communication is a fundamental and vital element in human life, as it is an essential part of human nature. Through communication, a person can form a framework of thought that serves as a guide in dealing with various situations encountered. In the current research, a qualitative research method with a descriptive approach is utilized. In this article, the literature review method is chosen to explore the role of interpersonal and group communication in the context of education. The method involves collecting, evaluating, and synthesizing relevant literature. The data used comes from journal articles, books, and various other sources related to the research topic. The importance of effective communication in supporting students in establishing good and sustainable relationships within the community is highlighted. This not only impacts group relationships but also relationships with individuals in the community environment. For us, the role of effective communication in building good and sustainable relationships is crucial. Effective communication enables strengthening social bonds, enhancing collaboration, solving problems, developing empathy, communicating information clearly, and developing leadership skills.